2013
DOI: 10.1002/art.37979
|View full text |Cite
|
Sign up to set email alerts
|

Acute Vibration Induces Transient Expression of Anabolic Genes in the Murine Intervertebral Disc

Abstract: Objective. Low-amplitude whole-body vibration has been adopted for the treatment of back pain and spinal disorders. However, there is limited knowledge of the impact of vibration on the intervertebral disc (IVD). This study was undertaken to examine the effects of acute vibration on anabolic and catabolic pathways in the IVD and to characterize the dependence of these changes on time and frequency.Methods. Custom-designed platforms were developed to apply acute vibration to ex vivo and in vivo mouse models. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…In contrast to other studies, we used LMHFV locally on the calvarial area, while the usual protocol in the earlier experiments was to subject the animal to whole body LMHFV [20, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other studies, we used LMHFV locally on the calvarial area, while the usual protocol in the earlier experiments was to subject the animal to whole body LMHFV [20, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…All procedures were approved by the Council on Animal Care at The University of Western Ontario, in accordance with the guidelines of the Canadian Council on Animal Care. Based on parameters of WBV used in clinical protocols, 10‐week‐old male CD‐1 mice were subjected to vertical sinusoidal vibration at a frequency of 45 Hz, with a peak‐to‐peak amplitude of 74 μm, and peak acceleration at 0.3 g for 30 minutes per day, 5 days per week, for 2 or 4 weeks, using a previously described vibration platform . Age‐matched controls were housed in identical chambers on a sham (nonvibrated) platform to replicate handling and environmental conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent study using mouse models demonstrated anabolic effects of a single exposure to WBV on the IVD . Therefore, we sought to determine whether the transient changes previously reported would result in long‐term beneficial effects on joint health.…”
mentioning
confidence: 97%
“…Oscillating up- and down-regulation trends with loading and resting suggest that changes in expression of matrix remodeling genes in IVD cells were transient as demonstrated in earlier studies [4446]. However, the trends of matrix anabolic and catabolic genes were different compared to the mentioned studies due to different models and experimental conditions.…”
Section: Discussionmentioning
confidence: 64%